Experimental and Numerical Investigation of Internal Explosion in an Earth-Covered Magazine - Guangan Xu; Yanyu Qiu; Huadao Xing; Xiaodong Li; Cheng Gong (Buildings, 2022)
Earth-covered magazine has some characteristics that are safer than the above-ground magazine and are more economical than underground magazine. To investigate the pressure distribution and the structural failure under the internal explosion, the scaled tests of the earth-covered magazine were conducted under a 0.5 kg TNT explosive charge. The overpressure in the 0°, 90°, and 180° directions outside the structure and the debris distribution were obtained. The numerical simulations were constructed in LS-DYNA software to analyze the test results. The results show that the external overpressure has a directional characteristic that the maximum and minimum overpressure appear in 0° and 180° directions, respectively. In the double logarithmic coordinate system, the overpressure peaks in three directions are linearly related to the scaled distance. Most of the fragments in the 0° direction hit the ground within the front range of ±60°, and the further fragments (40 m or more) were confined to a limited sector within the front range of ±30°. The internal explosion numerical simulation shows that the concrete cracks first appeared at the roof and the ground, and then the damage occurred at the intersection of the walls, and then the damage occurred at each surface. The maximum debris velocity of the side and rear walls is lower than that of the front wall due to the limitation of the soil. The motion equations of the debris combined with numerical simulation can be adopted to predict the projection distance of fragments.